The F-Word - Frisch, Katrin (Logos Verlag Berlin, 2019)
Ezra Pound, T. S. Eliot, and Wyndham Lewis have all, to varying degrees, been the subject of studies that explore their ideology. All too often, however, these studies have not tackled the issue adequately, limiting their analytical approach to fascism or other phenomena such as anti-Semitism. Frequently, they have also sought to exculpate these writers or to normalise their political tendencies in an effort to circumnavigate the dilemma of how to address the paradox of right-wing artists who are both harbingers and opponents of the imagined trajectory of progressive modernity. This interdisciplinary study analyses the connections between literary Modernism and right-wing ideology. Moreover, it is the first academic study to explore the reception of these Modernist authors by today's far right, seeking to understand in what ways they use strategic readings of Modernist texts to legitimise right-wing ideology. By raising fundamental questions about the relationship between aesthetics and politics, this study ultimately challenges its readers to see their cultural practices as political. It wants to make visible and problematize the interdependencies of right-wing ideology and cultural production as well as reception in order to explain the (far) Right as a phenomenon deeply rooted in European history and cultural development. It thus lays bare the misconceptions, the gaps as well as the complicity in the debate about right-wing ideology in literature.